CONTINUES IMPROVEMENT SEBAGAI UPAYA DALAM MENINGKATKAN MUTU PENDIDIKAN PEDESAAN - Rusdi, Rusdi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2018)
Continues Improvement is very important to improve everything, especially educational institutions, in improving the quality of rural education requires seriousness, because the institutions in rural areas are all good from infrastructure, teachers (teachers), quality of education, and so forth.Because of minimizing the lack of education in the village with education in the city, the author tries to provide solutions through Continues Improvement as an effort to stabilize the quality of education which is very concerning.There are several stages in improving the quality of education through Continues Improvement, which first determines problems, determines solutions, implements solutions, and evaluates, so that is the stage that a liaeder must do in improving the quality of education.